A study on the deep etching and ohmic contact process of 6H-SiC high-temperature pressure sensor. (March 2015) - Tang, Fei; Ma, Ximin; Wang, Xiaohao
In all the process steps of manufacturing high-temperature pressure silicon carbide sensors, deep etching and ohmic contact are two crucial processes. Reactive ion etching is used for the deep etching of silicon carbide in our experiment, and the surface has a high quality after etching. Using nickel as the mask material on the C layer by electroplating, the depth of deep etching reaches about 81 µm and the thickness uniformity is fairly good, fluctuating within 200 nm or less. The Ti–TiN–Pt system is proposed for metallization, in which Ti, TiN and Pt are used as the contact layer, the diffusion impervious layer and the lead interaction layer, respectively. The Kelvin test shows that stable ohmic contact is achieved and a specific contact resistivity of 8.42 × 10 −4 Ω cm 2 is detected. The etching depth of 81 µm meets the requirement of forming a sensitive circular membrane, and the metal system of Ti–TiN–Pt ensures reliable connection and stable ohmic contact between the metal and semiconductor at high temperatures.